The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2053951719842540
|View full text |Cite
|
Sign up to set email alerts
|

Are the dead taking over Facebook? A Big Data approach to the future of death online

Abstract: We project the future accumulation of profiles belonging to deceased Facebook users. Our analysis suggests that a minimum of 1.4 billion users will pass away before 2100 if Facebook ceases to attract new users as of 2018. If the network continues expanding at current rates, however, this number will exceed 4.9 billion. In both cases, a majority of the profiles will belong to non-Western users. In discussing our findings, we draw on the emerging scholarship on digital preservation and stress the challenges aris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…This expansion and consumption model has both supported and neglected the data of the dead, which both proliferates and languishes. For example, as researchers across disciplines have noted, the dead may soon outnumber the living on social media (Karppi, 2018;Öhman & Watson, 2019). But while questions about digital remains are "critically needed" (Öhman & Watson, 2019, pp.…”
Section: Sarah Welsh the University Of Texas At Austinmentioning
confidence: 99%
See 1 more Smart Citation
“…This expansion and consumption model has both supported and neglected the data of the dead, which both proliferates and languishes. For example, as researchers across disciplines have noted, the dead may soon outnumber the living on social media (Karppi, 2018;Öhman & Watson, 2019). But while questions about digital remains are "critically needed" (Öhman & Watson, 2019, pp.…”
Section: Sarah Welsh the University Of Texas At Austinmentioning
confidence: 99%
“…Increasing attention has been paid to technologies for grief, end of life, and digital possessions (Sas et al, 2019), and also to digital remains as big data (Karppi, 2018;Öhman & Watson, 2019). However, these perspectives often focus on the (important) question of how digital remains are mediated by corporate interests (as Facebook profiles especially), and less on the environmental impact of the mass-scale preservation required for such a model.…”
Section: Maintaining Digital Remainsmentioning
confidence: 99%
“…Consider, for instance, the increasing presence of deceased user profiles on social media, commonly referred to as digital human remains (Stokes, 2015). It has been predicted that within less than 50 years, Facebook may host more profiles belonging to deceased than living users (Öhman and Watson, 2019), meaning that past individuals now increasingly remain present in the spaces of the living. In scholarly literature, this co-presence has rightly been interpreted in terms of a collapsing time , where the present and the past implode into each other.…”
Section: The Ethical Significance Of Temporal Frictionmentioning
confidence: 99%
“…The most popular SNS worldwide -FB has been targeted ever since its establishment, by researchers of various fields, such as the communication, information and computer science, health sciences, and psychology, to find out their roles and functions in bereavement (Brubaker, Hayes, & Dourish, 2013;Carroll & Landry, 2010;DeGroot, 2012;Pennington, 2013;Rossetto, Lannutti, & Strauman, 2014). Additionally, O¨hman & Watson (2019) via their analysis applying the big data approach, concluded that the dead will outnumber the living on FB before the end of the century and they claimed digital remains or profiles of the dead may become invaluable collective historical records of present societies for future generations.…”
Section: Introductionmentioning
confidence: 99%